Exploring the Sports Experiences of Socially Vulnerable Youth - Super, Sabina (Social Inclusion, 2017)
Sports participation is considered beneficial for the development of socially vulnerable youth, not only in terms of physical health but also in terms of cognitive, social and emotional health. Despite the strong belief that sports clubs offer a setting for positive youth development, there is limited knowledge about how socially vulnerable youths experience their participation in these clubs. Interviews were conducted with 22 socially vulnerable youths that play a sport at a local sports club. An inductive content analysis was conducted and three themes were discovered that are included in the positive and negative sports experiences: the extent to which the youths experienced visibility of their skills, the extent to which the youths felt confident while playing their sport, and the extent to which the youths felt that sport was a challenge they liked to take on. More importantly, there was a fragile balance within each of the themes and the sports coaches played an important role in installing and maintaining a supportive environment in which the youths could have meaningful, consistent and balanced sports experiences. It is not self-evident that for socially vulnerable youth sports experiences are positive and supporting.